Paraprotein Sample Exchange in Australia and New Zealand – 2018 - Wijeratne, Nilika (Clin Biochem Rev, 2019)
Quantification of co-migrating paraproteins in the beta-region presents an ongoing challenge for laboratories performing serum protein electrophoresis. The between-laboratory variation may impact patient care if the patient uses different pathology services during plasma cell dyscrasia monitoring. To identify the practical difficulties and determine the extent of agreement in the reporting of beta-migrating paraproteins in Australia and New Zealand (NZ), sample exchanges were conducted in five Australian states and in NZ in early 2018. This study has highlighted the variation in quantification and reporting of beta-migrating paraproteins which could potentially affect patient monitoring and management.